2022
DOI: 10.3390/molecules27072179
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein and Αlpha-Tocopherol Inhibit Toll-like Receptor Pathways in Cisplatin-Induced Nephrotoxicity

Abstract: Cisplatin (CP) is a conventional chemotherapeutic agent with serious adverse effects. Its toxicity was linked to the stimulation of oxidative stress and inflammation. As a result, this study explored the protective effect of baicalein and alpha-tocopherol in nephrotoxicity induced by cisplatin. Until receiving an intraperitoneal injection of CP (3 mg/kg BW), rats were given baicalein orally 100 mg/kg for seven days or/and a single intraperitoneal injection of α-tocopherol 250 mg/kg. Renal function was tested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Some studies have shown that depletion of TLR2 is associated with protection and subsequent reductions in pro-inflammatory IL-17A in CIN, and especially when there is simultaneous inhibition of TLR4 expression or activity. However, there are also studies that connote to the opposite [92,93]. Reports on its role in CITs are limited though and it poses an intriguing area for further investigation, particularly since it is not clear which heterodimer is more involved in this process-TLR2/TLR1 or TLR2/TLR6.…”
Section: Pattern Recognition Receptors (Prrs) In Cisplatin-induced To...mentioning
confidence: 99%
“…Some studies have shown that depletion of TLR2 is associated with protection and subsequent reductions in pro-inflammatory IL-17A in CIN, and especially when there is simultaneous inhibition of TLR4 expression or activity. However, there are also studies that connote to the opposite [92,93]. Reports on its role in CITs are limited though and it poses an intriguing area for further investigation, particularly since it is not clear which heterodimer is more involved in this process-TLR2/TLR1 or TLR2/TLR6.…”
Section: Pattern Recognition Receptors (Prrs) In Cisplatin-induced To...mentioning
confidence: 99%
“…Baicalein has a molecular weight of 270.24 g/mol. Baicalein has been shown to improve disease severity by regulation of different disease-related proteins [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Therefore, before a comprehensive and mechanistic analysis of baicalein-mediated cancer chemopreventive properties, we present an overview of antibacterial, antiviral, and oxidative-stress-modulating activities of baicalein.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress plays an essential role in the pathogenesis of cisplatin-induced cytotoxicity, which indicates that the application of antioxidants can effectively ameliorate cisplatin-induced toxicity ( Mansour et al, 2006 ). For this purpose, past studies have demonstrated that various active extracts or active components obtained from herbal medicines have a significant activity in antagonizing the side effects caused by cisplatin ( Awadalla et al, 2022 ; Gholampour et al, 2022 ; Pei et al, 2022 ). According to literature reports, flavonoids extracted from Epimedii Folium can effectively resist the toxicity caused by cisplatin ( Ma et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%